Using the Liquid Crystal Spatial Light Modulators for Control of Coherence and Polarization of Optical Beams - Ostrovsky, Andrey S.; Rickenstorff-Parrao, Carolina; Olvera-Santamaría, Miguel Á. (IntechOpen, 2011)
None